Integrasi Literasi Keuangan Syariah dalam Kurikulum Pendidikan Tinggi: Kerangka Integratif - Kumaidi Kumaidi; Arna Saskia; Ade Rahayu; Hardiansyah Padli (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The rapid growth of Indonesia’s Islamic finance industry contrasts with persistently low Islamic financial literacy, particularly among university students as future professionals. This study aims to synthesize existing literature to develop an integrative framework for embedding Islamic financial literacy within higher education curricula, identify multi-level implementation barriers, and propose adaptive strategies aligned with digital transformation. Using a qualitative Systematic Literature Review (SLR), this study analyzes ten peer-reviewed publications published between 2021 and 2025 through content and thematic analysis. The findings indicate that effective integration requires a holistic curriculum design encompassing cognitive, affective, and psychomotor competencies, supported by institutional readiness, lecturer capacity, and multi-stakeholder collaboration. Major barriers emerge at the micro, meso, and macro levels, including superficial digital literacy, limited interdisciplinary expertise among lecturers, fragmented institutional policies, and weak coordination between academia, industry, and regulators. This study demonstrates that digital transformation offers strategic opportunities to strengthen Islamic financial literacy through interactive, experiential, and community-based learning, provided it is accompanied by the development of critical and ethical financial reasoning. The main contribution of this research lies in proposing an integrative framework that connects curriculum design, implementation barriers, and adaptive strategies within a value-based and digitalized education context, offering theoretical and practical implications for higher education institutions and policymakers.